Activation of KV7 channels stimulates vasodilatation of human placental chorionic plate arteries. Issue 6 (June 2015) - Mills, T.A.; Greenwood, S.L.; Devlin, G.; Shweikh, Y.; Robinson, M.; Cowley, E.; Hayward, C.E.; Cottrell, E.C.; Tropea, T.; Brereton, M.F.; Dalby-Brown, W.; Wareing, M.
Abstract: Introduction: Potassium (K + ) channels are key regulators of vascular smooth muscle cell (VSMC) excitability. In systemic small arteries, Kv 7 channel expression/activity has been noted and a role in vascular tone regulation demonstrated. We aimed to demonstrate functional Kv 7 channels in human fetoplacental small arteries. Methods: Human placental chorionic plate arteries (CPAs) were obtained at term. CPA responses to Kv 7 channel modulators was determined by wire myography. Presence of Kv 7 channel mRNA (encoded by KCNQ1-5 ) and protein expression were assessed by RT-PCR and immunohistochemistry/immunofluorescence, respectively. Results: Kv 7 channel blockade with linopirdine increased CPA basal tone and AVP-induced contraction. Pre-contracted CPAs (AVP; 80 mM K + depolarization solution) exhibited significant relaxation to flupirtine, retigabine, the acrylamide (S)-1, and (S) BMS-204352, differential activators of Kv 7.1 – Kv 7.5 channels. All CPAs assessed expressed KCNQ 1 and KCNQ 3-5 mRNA; KCNQ 2 was expressed only in a subset of CPAs. Kv 7 protein expression was confirmed in intact CPAs and isolated VSMCs. Discussion: Kv 7 channels are present and active in fetoplacental vessels, contributing to vascular tone regulation in normal pregnancy. Targeting these channels may represent a therapeutic intervention in pregnancies complicated by increased vascular resistance. Highlights: Kv 7 channels are present and active in fetoplacental vessels. Novel channel activators significantly relax isolated arteries. Targeted activation may improve blood flow in cases of increased placental vascular resistance.